Aporte e fragmentação de matéria orgânica em riacho neotropical - Cogo, Gláucia Bolzan (2012)
The objective of this study was to determine the plant alloctonous material input and its processing by shredders in the Caranguejo Creek, a first order Neotropical stream. In order to do so, three experiments were performed. To verify the plant alloctonous material input, five suspended and ten lateral leaf-collectors were installed in the study area. Two samplings were made each season of the year, with a total of approximately 15 sampling days for each season. Input was higher in the suspended collectors than in the lateral ones. There was no difference in input amongst the seasons, and the annual input was of 1.254 g.m-2.year-1. Leaves were the most abundant material, comprising 61,38% of the sample, followed by twigs (29,15%) and others (9,46%). To evaluate the role of decapod crustaceans in shredding, channels containing litter bags of Ficus luschnathiana leaves were placed within the creek. Two types of channels were used, one allowing the decapods to access the leaves, and the other preventing it. Both types had the litter bags accessible to other invertebrates that integrated the stream community. The leave s decomposition rate was faster in the presence of decapods, indicating their potential as shredders. Besides accelerating the decomposition rates, the presence of decapods altered the community composition and density of individuals associated with the litter bags. The density of the macroinvertebrates was higher in the absence of decapods. The most representative functional feeding group were the collectors. The typical shredders were represented by the families Gripopterygidae e Sericostomatidae, comprising 4% of the total. The decapods species found in the study area are the anomuran Aegla longirostri, in higher densities, and the crayfish Parastacus pilimanus. In order to verify the percentage of alloctonous leaves that A. longirostri is capable of processing, an experiment was conducted in the laboratory. Leaves of different species, collected in the creek, were offered to the individuals, and its consume recorded. There was no difference in leaf consumption between adults (males and females), but there was a difference among these and the juveniles. Adults consumed a mean of 0,0175 (± 0,005)g of leaves per day, and the juveniles consumed 0,010 (± 0,002)g/day. With the data concerning leaf input, the daily leaf consumption rates and the information on the density of the aeglids, at the study site, it was possible to estimate that this population of A. longirostri is able to process approximately 6,14% of the leaves that fall in the creek. These results show that Caranguejo Creek is a location that receives many types of vegetal organic matter, through input from the riparian vegetation, that will be consumed by the aquatic community. Besides, the area possesses low abundance of insect shredders, and therefore the decapod crustaceans present a highlighted importance as shredders.